Effect of Combined Paracetamol and Dexamethasone on Pain and Postoperative Nausea Vomiting - Ayu, Dian; Widowati, Apita Sekar; Riza, Mohamad (International Journal of Human and Health Sciences (IJHHS), 2020)
Background : Pain and Postoperative Nausea and Vomiting (PONV) are surgical side effects. Pain management can use opioids and non-opioids. Opioids have side effects such as nausea, vomiting, pruritus, somnolence, and respiratory depression, so other alternatives are needed to reduce pain. Paracetamol is an analgesic while dexamethasone is antiinflammatory and anti-emetic. This study was to determine whether the combination of paracetamol and dexamethasone was more effective in dealing with pain and PONV after cesarean section than paracetamol. Materials and Methods : This was an experimental study employing post-test only control group design, using two study groups. Group PD (combined paracetamol and dexamethasone) was treated using dexamethasone 8 mg and paracetamol 1 gram intravenously, while the group P (paracetamol) was treated using paracetamol 1 gram intravenously. Data of Pain and PONV were collected using the Wong Baker Faces Scale, Numeric Rating Scale, and a frequency table for PONV at the 4th, 6th, 12th, and 24th hours of postoperative administration. The data were analyzed using Mann Whitney test. Results : The results of this study found that the multimodal administration of combined paracetamol and dexamethasone was better in reducing the pain compared to administration of a paracetamol at 4th, 6th, 12th, and 24thhours of post cesarean section(p <0.05). Multimodal administration of combined paracetamol and dexamethasone was better reduced the incidence of PONV compared tothat of paracetamol at the 4thhour of post cesarean section(p <0.05). The multimodal use of combined paracetamol and dexamethasone had resulted fewer use of opioid and anti-emetic frequencies compared to that of paracetamol. Conclusion : The combined paracetamol and dexamethasone was more effective to reduce pain and PONV in samples with post cesarean section. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 184-188